GIG Economy: Emerging Trends and Challenges After Globalisation - Mohideen, A.J. Haja; Khatoon, Sogra; G Y, Shwetha; Singh, Sneha; Rafee, B. Mahammad (Journal of Neonatal Surgery, 2025)
Economic globalization, has significantly changed the patterns of employment in the 21st century. Due to technological progress and globalisation, the workforce is radically changing. A new set of expectations and attitudes about work are being brought about by the growth of the gig economy. One of the main reasons the gig economy is becoming more and more popular is the development of digital talent platforms that connect employers and employees. Workers in the gig economy face job insecurity, irregular income, and lack of benefits such as health insurance and pensions. The importance of gig economy is largely acknowledged in industrialized countries and it is also becoming popular in emerging economies. During COVID-19, gig helped many people by providing employment and a source of income. The expanding Gig economy benefits both the employers and workers in terms of low-cost labour, a more agile and adaptable workforce and freedom to choose projects, increased flexibility, autonomy, and diverse income streams respectively but the issues like Labour exploitation, Job security, Issues with payment, Regulatory framework and Lack of organizational support will pose challenges and questions the sustainability of Gig Economy. By building a strong professional development, and effective workforce management, gig workers and businesses can maximize the benefits of gig economy. Governments should come forward with strong legislations and frameworks to make the gig economy more viable. The gig economy must become more structured in order to become sustainable and integrated into a country's economy.